The Golden Age of the Company: (Three Colors of Company’s Time) - Brusov, Peter N.; Filatova, Tatiana; Orehova, Natali; Kulik, Veniamin (Journal of Reviews on Global Economics, 2015)
In this paper we investigate the dependence of attracting capital cost on the time of life of company n at various leverage levels, at various values of capital costs with the aim of define of minimum cost of attracting capital. All calculations have been done within modern theory of capital cost and capital structure by Brusov - Filatova - Orekhova (Brusov et al. 2011a,b,c,d,e; 2012 a,b; 2013 a,b,c; 2014 a,b; Filatova et al. 2008). It is shown for the first time that valuation of WACC in the Modigliani - Miller theory (Modigliani et al. 1958; 1963; 1966) is not minimal and valuation of the company capitalization is not maximal, as all financiers supposed up to now: at some age of the company its WACC value turns out to be lower, than in Modigliani - Miller theory and company capitalization V turns out to be greater, than V in Modigliani - Miller theory. It is shown that, from the point of view of cost of attracting capital there are two types of dependences of weighted average cost of capital, WACC, on the time of life of company n: monotonic descending with n and descending with passage through minimum, followed by a limited growth. The first type takes place for the companies with low capital costs of the company, characteristic for the western companies. The second type takes place for higher capital costs of the company, characteristic for the Russian companies as well as for companies from other developing countries. This means that latter companies, in contrast to the western ones, can take advantage of the benefits, given at a certain stage of development of company by discovered effect. Moreover, since the "golden age" of company depends on the company’s capital costs, by controlling them (for example, by modifying the value of dividend payments, that reflect the equity cost), company may extend the "golden age" of the company, when the cost to attract capital becomes a minimal (less than perpetuity limit), and capitalization of companies becomes maximal (above than perpetuity assessment) up to a specified time interval. Concluded that existed up to the present conclusions of the results of the theory of Modigliani-Miller (Modigliani et al. 1958; 1963; 1966) in these aspects are incorrect. We discuss the use of opened effects in developing economics (Brusov et al. 2015).